Clinicians' caseload management behaviours as explanatory factors in patients' length of time on caseloads: a predictive multilevel study in paediatric community occupational therapy - Kolehmainen Niina; MacLennan Graeme; Francis Jillian J; Duncan Edward AS (BMC, 2010)
Abstract Background Long waiting times and large caseloads are a challenge to children's therapy services internationally. Research in hospital-based healthcare indicates that waiting times are a function of throughput, and that length of care episode is related to clinicians' caseload management behaviour (i.e. actions at assessment, treatment, post-treatment, and discharge). There have been few attempts to study this in community health services. The present study investigated whether community occupational therapists' behaviour predicts children's length of time (LoT) on caseloads. Methods Retrospective survey of case notes of children recently discharged from occupational therapy services. Using cluster random sampling, case notes were drawn from therapy records in six NHSScotland Health Boards. Data about therapists' behaviours of assessing, treating, reviewing and discharging, together with child characteristics, were used to construct regression models of factors related to LoT. Results Twenty-six therapists [median(IQR) time in paediatrics 8(6-13) years] and 154 of their cases [mean(SD) age 7(3) years; median(IQR) LoT 10(3-21)] were included. A multi-level model, adjusting for clustering, for therapists' actions of communicating assessment outcomes to parents, providing treatment, and placing the child on review, and for a diagnosis of cerebral palsy, explained 44% of variation in LoT. Conclusions Occupational therapists' caseload management behaviours are associated with children's LoT on caseloads. Further research is required to investigate the direction of relationships between therapists' behaviours and LoT; and the relationships between contextual factors, therapists' caseload management behaviours and LoT. Further exploration of therapists' beliefs about caseload management could also be useful in identifying possible factors contributing to variation between therapists.